Avaliação de Cursos a partir do Sinaes: uma contribuição à Comissão Própria de Avaliação da Universidade Federal da Paraíba - Ribeiro, Wagner Leite (2018)
The main objective of this study is to analyze the information contained in the course evaluation reports, made available to the academic community and to the society, on the website of the Evaluation Committee (CPA) of the Federal University of Paraíba (UFPB). National System for the Evaluation of Higher Education (SINAES), in order to assist the CPA/UFPB in the orientations given to the coordination of courses in the procedures related to the evaluation of undergraduate courses and, in particular, to the on-site visits of the commissions of the National Institute of Educational Studies and Research Anísio Teixeira (INEP). In this sequence, elements were identified to support the organization of course coordination in the conduct of reconnaissance and renewal visits for the recognition of courses. Thus, the data collection was performed through an exploratory research through the bibliographical and documentary survey. For that, the technique used to treat the data collected was the SWOT analysis (Strenghts, Weaknesses, Opportunities, Threats). As a result, it was noticed that the Political-Pedagogical Projects of the Courses (PPCs) should be revised and updated in order to comply with the current legislation, in particular the guidelines established by the National Commission for the Evaluation of Higher Education (CONAES) and INEP/MEC. We also noted the importance of making improvements regarding aspects related to library, accessibility and other physical facilities, since such indicators were notoriously poorly evaluated in on-site visits.